Cardiometabolic self-care and their determinants among older adults in India: evidence from the Longitudinal Ageing Study of India - Shubhanjali Roy; Arka Ghosh; Saurav Basu (Clinical Epidemiology and Global Health)
Background: Cardiometabolic syndrome (CMS) is a major public health issue in India, driven by urbanization, unhealthy dietary shifts, and sedentary lifestyles. Optimal cardiometabolic self-care, as defined by the Healthy Longevity Heart Code (HLHC), is critical to slowing cardiovascular aging and improving health outcomes. Objective: To assess the prevalence and determinants of cardiometabolic self-care practices among older adults in India using HLHC proxies derived from the Longitudinal Ageing Study in India (LASI). Methods: This study conducted a cross-sectional analysis of 66,606 participants aged ≥45 years from LASI (2017–2018). HLHC proxies included dietary habits, physical activity, waist circumference, smoking, alcohol consumption, sleep quality, mental exercises, and social interactions. Logistic regression analysis was used to identify predictors of optimal self-care, and mediation analysis assessed the role of wealth in modulating these outcomes. Results: Only 34.3 % of participants exhibited optimal cardiometabolic self-care, with higher prevalence among females (40.04 %) compared to males (28.52 %). Predictors of optimal self-care included higher education, socioeconomic status, and urban residence. Wealth significantly mediated the relationship between socioeconomic factors and cardiometabolic health. Suboptimal practices such as high central obesity (64.13 % males; 41.59 % females) and poor mental and social engagement were prevalent. Tobacco use and alcohol consumption were notably higher among males, while females demonstrated better adherence to dietary and physical activity guidelines. Conclusions: Suboptimal cardiometabolic self-care remains a significant challenge among Indian adults aged ≥45 years, with notable gender and socioeconomic disparities. Interventions should prioritize education, equitable access to resources, and gender-specific strategies to enhance adherence to HLHC guidelines and improve cardiometabolic health outcomes.